Blinded by bodies: Elevated eating disorder symptomatology is associated with increased attentional priority for thin bodies. (December 2021) - Berrisford-Thompson, Jemima; Sayers, Sarah; Bell, Jason; Dondzilo, Laura; Kennedy, Briana L.
Highlights: Bodies can blind us from perceiving other stimuli presented in close succession. Non-thin bodies are prioritised in attention more than thin bodies in unselected females. Greater attention toward thin bodies is associated with elevated body dissatisfaction. Eating disorder-specific rumination mediates attentional priority for thin bodies. Abstract: Selective processing of female thin-ideal body imagery is associated with greater body dissatisfaction, and eating disorder-specific rumination has been shown to mediate this relationship. Across two studies, we employed a modified rapid serial visual presentation task (similar to that used within the emotion-induced blindness literature), such that participants searched for a task-relevant target that was sometimes preceded by a thin body, non-thin body, or neutral task-irrelevant distractor. Our first experiment ( N = 372) revealed a "body-induced blindness" in an unselected female sample, such that bodies in general distracted attention more than neutral images, and non-thin bodies distracted more than thin-ideal bodies. In our second experiment, female participants were selected based on eating disorder symptomatology ( N = 114). Females that exhibited elevated eating disorder symptoms were distracted more by thin bodies compared to those low in symptomatology, greater distraction from thin bodies was associated with greater body dissatisfaction, and this relationship was mediated by eating disorder-specific rumination. Altogether, our findings illustrate the persistent nature of attentional distortions that occur early in cognitive processing and across time for those high in eating disorder symptomatology.